2023
DOI: 10.3390/vaccines11050928
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for HPV Vaccine among Women Living with HIV in Nigeria

Abstract: Background: Human papillomavirus (HPV) is responsible for most cervical cancer cases globally, with women living with HIV having a higher risk of persistent HPV infection and HPV-associated disease. The HPV vaccine is a promising tool to reduce cervical cancer rates, but its uptake among women living with HIV in Nigeria is unknown. Methods: A facility-based, cross-sectional survey was conducted with 1371 women living with HIV to assess their knowledge of HPV, cervical cancer, and the HPV vaccine as well as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…As HPV vaccination is not covered by public insurance in Ghana, it appears that many WLHIV may be unwilling or unable to pay for it, as highlighted in a recent study conducted in Nigeria. 26 Thus, the cost of HPV vaccination may be a substantial barrier to its uptake, especially for women with lower incomes, which was the rural group in this study. We also observed that women screened in the rural setting were 12 times more likely to have undergone cervical screening than those screened in the urban setting.…”
Section: Discussionmentioning
confidence: 86%
“…As HPV vaccination is not covered by public insurance in Ghana, it appears that many WLHIV may be unwilling or unable to pay for it, as highlighted in a recent study conducted in Nigeria. 26 Thus, the cost of HPV vaccination may be a substantial barrier to its uptake, especially for women with lower incomes, which was the rural group in this study. We also observed that women screened in the rural setting were 12 times more likely to have undergone cervical screening than those screened in the urban setting.…”
Section: Discussionmentioning
confidence: 86%
“…Groundbreaking studies demonstrate its safety and effectiveness against a gamut of potentially life-altering HPV-related health conditions. From cervical cancer to many other perilous maladies, the vaccine is an epoch-making beacon of hope and renewal for the female populace embroiled in this battle [31,32].…”
Section: I) Hpv Vaccinementioning
confidence: 99%